PENGARUH KESIAPAN BELAJAR DAN KOMUNIKASI PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS X IPS SMA NEGERI 9 KOTA JAMBI - Diliza Afrila, Rada Apriliani, (SJEE (Scientific Journals of Economic Education), 2019)
Abstract This study aims to determine (1) the effect of learning readiness on student learning outcomes in Economics subjects in class X IPS SMA Negeri 9 Jambi City, (2) the influence of learning communication on student learning outcomes in economic subjects in Class X IPS SMA Negeri 9 Kota Jambi, (3) the effect of learning readiness and learning communication on student learning outcomes in Economics in Class X IPS SMA Negeri 9 Jambi City. The results showed that (1) Learning Readiness influences student learning outcomes in Economics class subjects in X IPS SMA Negeri 9 Jota Jambi. This is indicated by the value of tcount> ttable namely, 2.219 > 1.984, (2) Learning Communication influences student learning outcomes in Economics subjects in class X IPS SMA Negeri 9 Jambi City. This is indicated by the value of tcount> ttable, which is 2.600 > 1.984 and (3) Learning readiness and learning communication influences the learning outcomes of students in Economics subjects in class X IPS SMA Negeri 9 Jambi City. This is indicated by the value (Fcount> Ftable, which is 3.586> 3.04) Keywords : Learning Readiness, Communication, Outcomes